Mental health and early adolescent: a prevalence study - Abd. Aziz, Karimah Hanim; Jamani, Nurjasmine Aida; Aziz, Nur Wal Affa; Hamzah, Fatin Shahira (Kulliyyah (Faculty) of Medicine, International Islamic University Malaysia, 2018)
Prevalence of mental health problems among children and adolescent is increasing in trend as reported in the National Health Morbidity Survey (NHMS). Male, younger age group and from low socioeconomic status were at higher risk to develop this problem. This study aimed to measure the prevalence of mental health problems and their associated factors among young adolescent in Kuantan, Pahang.